Aliskiren improves endothelium‐dependent relaxation of thoracic aorta by activating PI3K/Akt/eNOS signal pathway in SHR. (April 2016) - Gu, Yue; Tang, Xin; Xie, Liping; Meng, Guoliang; Ji, Yong
Summary: Aliskiren, a direct renin blocker, has been approved for the treatment of hypertension. However, the potential role of aliskiren on vascular endothelial function in spontaneously hypertensive rats (SHR) remains unclear. In the present study, male SHRs at 12 weeks of age were orally administrated 30 mg/kg per day or 60 mg/kg per day aliskiren. After a 4‐week treatment, aliskiren showed a significant effect on the reduction of blood pressure at a dosage of 60 mg/kg per day, but not of 30 mg/kg per day. Moreover, both dosages of aliskiren improved endothelium‐dependent relaxation, reduced dihydroethidium fluorescence intensity, decreased level of malondialdehyde but heightened total antioxidant capacity and superoxide dismutase activity in thoracic aorta in SHR. Aliskiren also markedly increased expression of p85 α, an important subunit of phosphatidylinositol 3 kinase (PI3K), enhancing phosphorylation of protein kinase B (Akt) at Ser473 and endothelial nitric oxide synthase (eNOS) at Ser1177, as well as cyclic guanosine‐3′5′‐monophosphate (cGMP, a sensitive index of biological activity of nitric oxide) concentration. Furthermore, both anti‐oxidative and endothelium protective effects of aliskiren were diminished when PI3K was inhibited in vivo . The data presented here indicates that, aliskiren improves endothelium‐dependent relaxation of thoracic aorta in SHR, predominantly through attenuating oxidative stress and activation of the PI3K/Akt/eNOS pathway. These data might propose novel strategies to prevent and improve vascular endothelial dysfunction.